(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2023)
This paper examined the purchasing power parity (PPP) theory for a group of sixteen developed countries using powerful statistical panel data methods that account for cross-sectional dependence. The paper utilized the Pesaran panel unit root test, the cointegration test of Westerlund, the Augmented Mean Group (AMG) estimator, the Common Correlated Effect Mean Group (CCEMG) estimator, and the panel data Granger non-causality test of Dumitricus and Hurlin to analyze the causal relationships among the variables involved in the study. The tests showed that the PPP theory occurs in this group of countries. Furthermore, outcomes of the long-run estimation revealed both depreciation and appreciation of the nominal exchange rates. Apart from providing important policy implications on the results obtained, this paper made another significant contribution by extending the linear AMG and CCEMG estimators into nonlinear estimators and further used them in examining the long-run PPP theory.